InGaAs/AlInAs/InP Quantum-Cascade Lasers with Reflective and Antireflective Optical Coatings - Podgaetskii, K. A.; Lobintsov, A. V.; Danilov, A. I.; Ivanov, A. V.; Ladugin, M. A.; Marmalyuk, A. A.; Kuznetsov, E. V.; Dyudelev, V. V.; Mikhailov, D. A.; Chistyakov, D. V.; Kognovitskaya, E. A.; Losev, S. N.; et al. (Bulletin of the Lebedev Physics Institute, 2024)
Quantum-cascade lasers (QCLs) based on InGaAs/AlInAs/InP with reflective and antireflective coatings are fabricated and studied. The manufactured lasers emit in the spectral range from 4 to 5 μm. The effect of variation in the front mirror reflectance on the output power of a QCL with a highly reflective rear mirror is investigated. It is shown that the use of an antireflective coating on the front face leads to a simultaneous increase in both the threshold current of the QCL and the slope of the light–current characteristic. This allows a higher output power to be achieved at high pump currents. In contrast, the use of a partially reflective coating on the front face not only reduces the threshold current of the QCL, but also decreases the slope of the light–current characteristic. Such QCLs may have an advantage over other emitters at low pump currents.